The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/ijerph16203855
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Matter Exposure and Under-Five and Maternal Deaths in Asia

Abstract: The Asian region is one of the major emission sources of air pollution. Although ambient PM2.5 has been linked to several health risks in high-, low-, and middle-income countries, the further analysis of type impact is still rare but significant. The PM2.5 distribution retrieved from MODIS (Moderate Resolution Imaging Spectroradiometer) aerosol optical depth products within 16 years thus explored the associations between under-five and maternal mortality for 45 countries in Asia. Both the nonparametric (Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…The thrust towards achieving higher economic growth in the sampled countries is resulting in deteriorated environmental conditions, pushing increased air pollution (PM 2.5 ) and consequent serious health threats. Our results are corroborated by the studies of [ 5 , 15 , 16 ], who highlighted a significant relationship between air pollution (PM 2.5 ) and child mortality. The studies in India, China [ 20 , 27 ], and other developing countries [ 3 , 13 , 28 ] have also established a significant relationship between air pollution and health outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The thrust towards achieving higher economic growth in the sampled countries is resulting in deteriorated environmental conditions, pushing increased air pollution (PM 2.5 ) and consequent serious health threats. Our results are corroborated by the studies of [ 5 , 15 , 16 ], who highlighted a significant relationship between air pollution (PM 2.5 ) and child mortality. The studies in India, China [ 20 , 27 ], and other developing countries [ 3 , 13 , 28 ] have also established a significant relationship between air pollution and health outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown a positive relationship between air pollution (PM 2.5 ) and child mortality in recent years. For example, Lien et al and Owili et al [ 15 , 16 ] showed a positive relationship of air pollution (PM 2.5 ) with child mortality in those under five and maternal deaths in 45 Asian countries and Africa. Gouveia et al [ 9 ] evaluated the impact of air pollution on child mortality in four Latin American cities (Mexico city, Santiago, Chile and Rio de Janeiro) using the generalized additive model with Poisson regression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, there is little evidence of the health effects of discriminated PM 2.5 (i.e., the major component of PM 2.5 ) , which may uniquely contribute to the global burden of disease. Currently, there are limited studies that have estimated the effects of discriminated or categorized ambient PM 2.5 , that is, anthropogenic, biomass and dust, on under-five and maternal mortality using satellite measurements, and these studies found a positive association in Africa 5 and Asia 7 . However, these studies 5 , 7 were regional and may not reflect the spatial variations throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas, populations such as the poor, elderly, and children are especially prone to pollution-related diseases, including respiratory illnesses, heart disease, cancer, etc. [3][4][5][6][7][8][9][10][11][12]. Pollution generates other serious environmental problems such as climate change or global warming, which also have important health consequences [13,14].…”
Section: Introductionmentioning
confidence: 99%